DETERMINATION OF BACKGROUND AND THRESHOLD FOR GOLD ON THE BOMBURI CONCESSION, NORTH-WESTERN GHANA (Journal of Science and Technology, 2016)
During the course of a mineral exploration programme by Ashanti-AGEM Alliance on the Bomburi Concession, northwest Ghana, about 2234 soil geochemical reconnaissance results for gold only were obtained as part of a multimedia sampling survey over defined stream anomalies. The results were based upon the minus 120-micron fraction by fire assay/AAS. In an attempt to establish the background and threshold of gold distribution on the concession, the soil results were grouped based on lithology into Cape Coast Granites (GI), Dixcove granites (G2) and Quartz-mica schist (QS) areas and statistical performed. The determined statistical parameters of gold for the three different lithologies and the total database (TD) (i.e. a combination of G1, G2 and QS) were similar being positively skewed and multi-modal. The relative cumulative frequency curves for the four datasets also have similar characteristics of many bends representing possibly, several populations. The background levels for G1, G2 and TD were determined to be 22, 30, 25 and 18 ppb, respectively. In view of the fact that the statistical parameters were similar, geological contacts could be potential sources of mineralisation, a background and threshold of 18 and 25 ppb, respectively were established for the Bomburi Concession.